Ovarian Cancer Chemotherapy: Targeted Drug Conjugate Systems - Ogundipe, Omotola D.; Olajubutu, Oluwabukunmi; Adesina, Simeon K. (Pharmaceutical Research - Recent Advances and Trends Vol. 1, 2024)
This chapter discusses advances in ovarian cancer chemotherapy. Ovarian cancer is one of the deadliest diseases that affect women worldwide. Unfortunately, most women with ovarian cancer receive a diagnosis when the disease has progressed to stages 3 or 4, which makes recovery from the disease difficult. The likelihood of survival is increased in women with early-stage disease who are able to commence treatment early as a consequence of early detection. While the majority of the patients respond well to first-line treatment, i.e. cytoreductive surgery integrated with platinum-based chemotherapy, the rate of disease recurrence is very high and the available treatment options for recurrent disease are not curative. Thus, more potent ovarian cancer therapy options are therefore required. In the fight against ovarian cancer, targeted drug conjugate systems have become a potentially effective therapeutic approach. With the help of these systems, it is possible to administer chemotherapeutic agents to ovarian cancer while protecting healthy cells. To promote the clinical translation of these drug conjugate systems, it is important to develop and utilize improved pre-clinical tumor models that more accurately mimic ovarian tumors in humans during the preclinical phase of drug development. Additionally, targeted drug conjugate systems improve therapeutic efficacy by facilitating drug accumulation in the tumor and minimizing the incidence of adverse effects. In this chapter, different targeted drug conjugate systems that have been developed or are being developed for the treatment of ovarian cancer are discussed.